2020
DOI: 10.1128/jcm.01906-19
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Microarray Gene Expression Signatures for Early Melioidosis Diagnosis

Abstract: Melioidosis is caused by Burkholderia pseudomallei and is predominantly seen in tropical regions. The clinical signs and symptoms of the disease are nonspecific and often result in misdiagnosis, failure of treatment, and poor clinical outcome. Septicemia with septic shock is the most common cause of death, with mortality rates above 40%. Bacterial culture is the gold standard for diagnosis, but it has low sensitivity and takes days to produce definitive results. Early laboratory diagnosis can help guide physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…More importantly, no significant overlap between genes that are differentially expressed between B. pseudomallei and other infections was found, even when Staphylococcus aureus and Staphylococcus coagulase negative were removed. Analogue to our findings, Sangwichian et al found that two other bacterial infections were falsely identified as B. pseudomallei by real-time PCR, suggesting that it is difficult to differentiate melioidosis from other pathogenic infections by transcriptional analysis [ 20 ].…”
Section: Resultssupporting
confidence: 80%
“…More importantly, no significant overlap between genes that are differentially expressed between B. pseudomallei and other infections was found, even when Staphylococcus aureus and Staphylococcus coagulase negative were removed. Analogue to our findings, Sangwichian et al found that two other bacterial infections were falsely identified as B. pseudomallei by real-time PCR, suggesting that it is difficult to differentiate melioidosis from other pathogenic infections by transcriptional analysis [ 20 ].…”
Section: Resultssupporting
confidence: 80%
“…Tan and colleagues confirmed that 60% of acute or subacute melioidosis patients presented antibodies against TssM in the sera within 2 weeks after hospital admission [22]. Hemolysin-coregulated protein (Hcp1) is a serological candidate target that was previously developed for lateral-flow rapid diagnosis [9,11] and ELISA [31]; however, our findings demonstrate that the Hcp1 performances (sensitivity, NPV, and accuracy) and method agreement (k) are lower than TssM. No previous report has ever directly compared the potential of TssM and Hcp1 for melioidosis diagnosis in the same approach.…”
Section: Discussionmentioning
confidence: 98%
“…The disadvantages of the serodiagnosis of BipD are the cross-reaction of BipD with other antibodies, the high seropositivity among the healthy population, and the fact that not all patients infected with B. pseudomallei produce sufficient levels of antibodies against BipD [ 64 , 66 ]. The main drawback of all the serological assays is that the antibodies can only be detected 7–14 days post-infection [ 33 ]. Thus, antibody-detection methods cause delays in both the diagnosis and treatment of melioidosis.…”
Section: Contentmentioning
confidence: 99%
“…With regards to molecular methods, many types of polymerase chain reactions (PCRs) conducted by targeting various genes to detect B. pseudomallei have resulted in different limits of detection (LODs) [ 31 , 32 , 33 ]. PCR can produce false-negative results when tested on direct blood specimens due to low bacterial loads (<10 CFU/mL), which are usually below the detection limits of any PCR assay, and the presence of inhibitory substances in the blood [ 22 ].…”
Section: Introductionmentioning
confidence: 99%